The effects of nutrition on maternal mortality: Evidence from 19th-20th century Italy. (December 2020) - Manfredini, Matteo
Abstract: The role of nutrition on maternal mortality has been long debated in the historical and scientific literature. Some scholars refute any role of nutrition and diet in the decline of maternal mortality, privileging other causes such as the diffusion of professional midwifery and medical and scientific progress, while others are more open-minded about some possible nutritional effects. The present paper investigates the relationship between maternal mortality and nutrition in Italy between 1887 and 1955 with the purpose to provide new elements and new data to the knowledge of such an association. Using time-series techniques on the official data provided by the National Institute of Statistics, the analysis demonstrates that the trend of maternal mortality was affected by both long- and short-term dynamics of the average daily caloric intake of the Italian population once controlled for the economic situation, here proxied by the annual time series of the GDP per capita. The same analysis clarifies that the impact of nutrition is just one element of a complex picture in which the major role is played by medical advances and scientific progress. The introduction of sulphonamides, in the second half of the thirties of the twentieth century, emerges, in fact, as the turning point in the fight against maternal death. Highlights: Scientific advances strongly affected the trend of maternal deaths in Italy. Nutrition had a role in the decline of maternal mortality once controlled for GDP per capita. Both the short and long dynamics of daily calorie intake affected maternal mortality. The GDP per capita did not show any significant effect on maternal mortality.